ZnO on nickel RF micromechanical resonators for monolithic wireless communication applications. (23rd March 2017) - Wei, Mian; Avila, Adrian; Rivera, Ivan; Baghelani, Masoud; Wang, Jing
Abstract: On-chip integrability of high- Q RF passives alongside CMOS transistors is crucial for the implementation of monolithic radio transceivers. One of the most significant bottlenecks in back-end-of-line (BEoL) integration of MEMS devices on CMOS processed wafers is their relatively low thermal budget, which is less than that required for typical MEMS material deposition processes. This paper investigates electroplated nickel as a structural material for piezoelectrically-transduced resonators to demonstrate ZnO-on-nickel resonators with a CMOS-compatible low temperature process for the first time. Aside from the obvious manufacturing cost benefit, electroplated nickel is a reasonable substitute for polycrystalline or single crystal silicon and thin-film microcrystalline diamond device layers, while realizing decent acoustic velocity and moderate Q . Electroplated nickel has been already adopted by MEMSCAP, a multi-user MEMS process foundry, in its MetalMUMPs process. Furthermore, it is observed that a localized annealing process through Joule heating can be exploited to significantly improve the effective mechanical quality factor for the ZnO-on-nickel resonators, which is still lower than the reported AlN resonators. This work demonstrates ZnO-on-nickel piezoelectrically-actuated MEMS resonators and resonator arrays by using an IC compatible low temperature process. There is room for performance improvement by lowering the acoustic energy losses in the ZnO and nickel layers.